2012
DOI: 10.1093/infdis/jis497
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1/2 Clinical Trial Evaluating Safety and Immunogenicity of a Varicella Zoster Glycoprotein E Subunit Vaccine Candidate in Young and Older Adults

Abstract: In this study, HZ/su adjuvanted subunit vaccine was well tolerated and more immunogenic than a live attenuated VZV vaccine. Clinical Trial registration. NCT00492648 and NCT00492648.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
108
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 30 publications
14
108
0
1
Order By: Relevance
“…This finding is consistent with the results of ZOE-50, in which vaccine efficacy against herpes zoster was found to be similar in all age groups (50 to 59, 60 to 69, and ≥70 years of age), but it contrasts with the efficacy of the approved live attenuated vaccine (Zostavax), which was found to decline with increasing age: 70% in adults 50 to 59 years of age, 64% in adults 60 to 69 years of age, 41% in adults 70 to 79 years of age, and 18% in adults 80 years of age or older. 24,25 In the Shingles Prevention Study, the live attenuated herpes zoster vaccine appeared to provide additional protection against postherpetic neuralgia beyond preventing herpes zoster (among adults 60 years of age or older, 51% vaccine efficacy against herpes zoster vs. 67% vaccine efficacy against postherpetic neuralgia).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with the results of ZOE-50, in which vaccine efficacy against herpes zoster was found to be similar in all age groups (50 to 59, 60 to 69, and ≥70 years of age), but it contrasts with the efficacy of the approved live attenuated vaccine (Zostavax), which was found to decline with increasing age: 70% in adults 50 to 59 years of age, 64% in adults 60 to 69 years of age, 41% in adults 70 to 79 years of age, and 18% in adults 80 years of age or older. 24,25 In the Shingles Prevention Study, the live attenuated herpes zoster vaccine appeared to provide additional protection against postherpetic neuralgia beyond preventing herpes zoster (among adults 60 years of age or older, 51% vaccine efficacy against herpes zoster vs. 67% vaccine efficacy against postherpetic neuralgia).…”
Section: Discussionmentioning
confidence: 99%
“…2,18,19 An investigational herpes zoster subunit vaccine (HZ/su; GSK Vaccines) containing VZV glycoprotein E and the AS01 B adjuvant system is being evaluated for the prevention of herpes zoster and postherpetic neuralgia in adults 50 years of age or older. [20][21][22][23][24][25] A previous trial (Zoster Efficacy Study in Adults 50 Years of Age or Older showed that HZ/su had a vaccine efficacy against herpes zoster of 97.2%, which was consistent across all age groups. 26 Although 24% of the participants in ZOE-50 were 70 years of age or older, the trial was not intended to definitively assess vaccine efficacy against herpes zoster or postherpetic neuralgia in this age group.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…A pivotal phase III study to assess the efficacy of the investigational vaccine for the prevention of shingles has met its primary endpoint and showed that HZ/su reduced the risk of shingles by 97.2% in adults aged 50 y and older compared with placebo. 93 An efficacy study on this vaccine (the Zoster Efficacy study ZOE-50), which was initiated in August 2010, is ongoing in 18 countries and involves more than 16,000 individuals.…”
Section: Zoster Vaccinationmentioning
confidence: 99%
“…113 The adjuvanted VZV gE subunit vaccine will be the vaccine of choice for immunocompromised persons. 93 …”
Section: Varicella (V) and Zoster Vaccinationmentioning
confidence: 99%